2017
DOI: 10.1364/boe.8.001889
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a spectral light scattering method to differentiate large from small particles in intraocular lenses

Abstract: Abstract:A psychophysical approach has been designed to measure straylight from intraocular lenses (IOLs) in vitro. This approach uses a clinical straylight meter (C-Quant) and an observer's eye as optical detector. Based on this, we introduced a method for study of straylight-wavelength dependency for IOLs. This dependency can be used to distinguish between 2 types of scattering particles (small and large) as defined by Mie theory. Validation was performed using a turbidity standard and scattering filters. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Hence, only straylight of the lens under test was measured. 21,22 In this manner, the straylight measured in vitro directly corresponds to the straylight (increase) experienced by the patient.…”
Section: Straylight Assessmentmentioning
confidence: 97%
See 3 more Smart Citations
“…Hence, only straylight of the lens under test was measured. 21,22 In this manner, the straylight measured in vitro directly corresponds to the straylight (increase) experienced by the patient.…”
Section: Straylight Assessmentmentioning
confidence: 97%
“…2, 5, 9-12, 17, 18 Although numerous studies on histological examination have been performed, 2, 5, 7, 9-12, 17, 18 little can be found on the optical quality of the affected IOLs. 7,11 The optical performance of opacified lenses has been studied by means of light scattering (straylight) measurements, [21][22][23] and quality metrics derived from the point spread function, such as the modulation transfer function (MTF) and the Strehl ration (SR). [24][25][26][27] Studies on straylight from different types of IOL opacification such as calcification, snow-flake degeneration, and glistenings, have shown that straylight is a very sensitive measure to detect the presence of IOL pathology.…”
Section: Endothelial Keratoplasty (Ds[a]ek) Andmentioning
confidence: 99%
See 2 more Smart Citations
“…[102][103][104][105][106][107][108] Often the problem shows up clearly in the slit lamp image, but not always. 109…”
Section: Dot-like or Localised Opacitiesmentioning
confidence: 99%